1984–2014. Normal Accidents. Was Charles Perrow Right for the Wrong Reasons?. (26th June 2015) - Le Coze, Jean‐Christophe
<x xml:space="preserve">Abstract</x> In 1984, Charles Perrow released the landmark book Normal Accident (NA), in which he argued the inevitability of accidents in certain types of high‐risk systems.The aim of this article is to reconsider the book, 30 years after its publication, and offer a new interpretation of its points. The message of the book seems as compelling as ever today: Accidents and catastrophes have continued to occur over the last three decades. However, the technological determinism of the book has been criticized and shown to be too restricted to account for the social nature of the phenomena. This article uncovers and highlights a second underlying message of the book which could arguably be the book's most valuable and compelling contribution.